Epidemiology and impact of bloodstream infections among kidney transplant recipients: A retrospective single‐center experience. Issue 1 (19th January 2018) - Shendi, Ali M.; Wallis, Gabriel; Painter, Helena; Harber, Mark; Collier, Sophie
Abstract: Background: Bloodstream infection (BSI) represents an important source of morbidity and mortality, as well as an increasing therapeutic challenge, among solid organ transplant recipients. Understanding the epidemiological and microbiological characteristics of BSI following renal transplantation is paramount to the implementation of appropriate preventative and therapeutic measures. Methods: We conducted a retrospective review of all BSI episodes occurring between July 2009 and April 2016 in adult patients, who received a renal transplant at Royal Free London hospital. Results: A total of 116 episodes of BSI occurred in 87 patients, 43 (49.4%) of them men. The mean age at BSI was 54.37 ± 12.81 years. Late‐onset BSI (>12 months post transplant) represented 55.2%, with the median time to BSI being 16.28 month. Sixty‐seven patients had single BSI and 20 had recurrent episodes. Enterobacteriaceae were responsible for 73.7% of BSI, with Escherichia coli the commonest causative organism (46.6%). The urinary tract was the most frequent source of infection in 56.9%. Among the E. coli infections, 100% of the tested isolates were sensitive to meropenem, ertapenem, tigecycline, and fosfomycin, and >90% were sensitive to piperacillin‐tazobactam, amikacin, and colistin. Lower susceptibility rates were encountered for ceftriaxone (70.6%), amoxicillin‐clavulanic acid (48.1%), cotrimoxazole (40.4%), trimethoprim (37.3%), and amoxicillin (21.6%). During BSI, the median serum creatinine increased from a reference of 131 μmol/L to a peak of 219 μmol/L. Acute kidney injury (AKI) complicated 75/116 BSI episodes (64.7%)—stage 1: 34, stage 2: 31, and stage 3 AKI: 10 episodes. After 3 months, the median creatinine remained elevated at 146 μmol/L. The 3‐month mortality rate was 8% (7/87), and the death‐censored graft loss was 6.9% (6/87). No significant difference was seen between BSI of urinary and non‐urinary sources in the incidence of AKI (χ 2 = 0.24, P = .6) or the percentage of creatinine change between baseline and peak and 3‐month creatinines ( P = .2 and .7 respectively). Conclusions: Urinary tract infection remains the commonest source of systemic infection among kidney transplant recipients and resistance to commonly used frontline antibiotics is common; thus, prevention and early detection are paramount. The appropriate choice of initial empirical antibiotic is vital to improve the outcome. Each unit needs to understand the epidemiology of organisms causing BSI in their transplant patients and their antibiotic susceptibilities.